Revisión de las especies de Panicum sect. Dichotomiflora (Poaceae: Panicoideae: Paniceae) - Zuloaga, Fernando Omar (2022)
Panicum sect. Dichotomiflora comprises a complex of annual and perennial species, distributed all over the world. They are characterized by its glabrous, ellipsoid to ovoid or lanceolate spikelets, with the lower glume 1/6 to 1/4(-1/3) the length of the spikelet, nerveless to 3-nerved, and upper glume and lower lemma subequal, 7-11(-13)-nerved. A total of 20 species are recognized in the section: Panicum aquaticum, P. dichotomiflorum, P. gilvum, P. impeditum, P. lacustre, P. laevinode, P. luzonense, P. madipirense, P. mlahiense, P. obseptum, P. paludosum, P. perangustatum, P. pilgerianum, P. porphyrrhizos, P. schinzii, P. subalbidum, P. sublaeve, P. sumatrense, P. trichonode, and P. vaseyanum. Also, lectotypes are designated for Panicum hygrophilum, P. ingens, P. lacustre, P. longiramum, P. oryzetorum, P. madipirense, P. porphyrrhizos, P. praelongum, P. proliferum var. longijubatum, and P. telmatodes. A geographic analysis of the species is presented, together with illustrations, and a key for the species. Additional comments on morphology of sect. Dichotomiflora are also included.